The Relationship Between Environmental Sanitation Facilities and the Risk of Stunting at the Pahandut Palangkaraya Community Health Center - Lia Gustri Maulisazen Basuki; Ani Margawati; Martha Irene Kartasurya (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Stunting is a picture of stunted growth caused by long-term malnutrition. The prevalence of stunting in Palangkaraya City is 23.59%, and the highest percentage of stunting in Palangkaraya City is in the Pahandut Palangkaraya Health Center (32.37%). One of the factors causing stunting is environmental sanitation facilities that do not meet health requirements. This study aims to determine the risk factors for stunting in environmental sanitation facilities in the working area of the Pahandut Palangkaraya Health Center. The type of research used is an analytical survey with a case-control design. The study was conducted in January-February 2023. The under-five population is 1,499 children. The study subjects were children aged 6-24 months, consisting of 38 stunted and 38 non-stunted children. Child body length data were measured using an infantometer and calculated using anthropometric standard deviation. Data on environmental health facilities were obtained from interviews and observations using questionnaires. The Odd Ratio test analyzed the data. Results of analysis of drinking water sources (OR=2.9, 95%CI=1.086-7.744), clown feces handling (OR=3.03, 95%CI=1.174-7.831), sewerage (OR=3.37, 95CI%=1.17 -7.831), toilet facilities (OR=3.2, 95%CI=1.23-9.23). Drinking water that does not meet health requirements is a risk factor, respondents do not have septic tanks, or sewerage is a risk factor for stunting, private wastewater disposal facilities and toilets that do not meet the requirements, and poor handling of clown faeces is a risk factor for stunting in the work area of the Pahandut Palangkaraya Health Center. Advice for public health centers is expected to monitor newborn children up to the first 1000 days of life to prevent malnutrition that causes stunting and aspects of stunting prevention in children.Keywords: Environmental, facilities, sanitation, stunting